Supramolecular Assembly and Reversible Transition and of Chitosan Fluorescent Micelles by Noncovalent Modulation - An Liu; Hong Song; Puyou Jia; Ying Lin; Qingping Song; Jiangang Gao (Advances in Polymer Technology)
Chitosan-based intelligent artificial systems have been of increasing interest for their biocompatibility, multifunctionality, biological activity, and low cost. Herein, we report the fabrication of supramolecular nanoparticles based on water-soluble chitosan (WCS) and 1,1′,1″,1″′-(ethene-1,1,2,2-tetrayl)tetrakis(benzene-4,1-diyl) tetrakis(azanediyl)tetraacetic acid (TPE-(N-COOH)4), which is capable of reversible transition between polyion complexes (PICs) and hydrogen bonding complexes (HBCs) with tunable aggregation-induced emission driven by pH value. The PIC micelles could be formed via electrostatic interaction between ammonium cations and carboxylate anions under mild alkaline conditions. The formation of the micelles dramatically blocks the nonradiative pathway and enhances the fluorescence of TPE moieties, and the maximum fluorescence intensity was achieved near the isoelectric point due to the restriction of intramolecular motion. In addition, the fluorescence intensity and size of the PIC micelles exhibited a temperature response in the range from 20 to 80°C. Upon adjusting the solution pH to 2, the PIC micelles were reconstructed into hydrogen-bonding complexes while the hydrogen bonding interaction between the protonated carboxyl groups of TPE-(N-COOH)4 and chitosan. Moreover, the size of the micelles underwent a remarkable decrease, whereas the fluorescence emission was further enhanced by ~6.25-fold. The pH actuated micellar transition from PIC to HBC with tunable fluorescence performance is fully reversible. This study provides novel multifunctional materials that are of great importance for their potential application in the fields of optoelectronic devices and chemical and biomedical sensors.